Mutual mediation effects of homocysteine and PCSK9 on coronary lesion severity in patients with acute coronary syndrome: interplay with inflammatory and lipid markers - Ping Jin; Juan Ma; Peng Wu; Yitong Bian; Xueping Ma; Shaobin Jia; Qiangsun Zheng (Lipids in Health and Disease)
Abstract Background Homocysteine (Hcy) and the proprotein convertase subtilisin/kexin type 9 (PCSK9) significantly contribute to atherosclerosis (AS) as well as coronary lesion severity. Our previous work demonstrated that Hcy upregulates PCSK9, accelerating lipid accumulation and AS. A PCSK9 antagonist reduces plasma Hcy levels in ApoE−/− mice. These findings suggest complex roles for both Hcy and PCSK9 in AS. This study investigated the mutual mediating influence of Hcy together with PCSK9 on coronary lesion severity among individuals diagnosed with acute coronary syndrome (ACS), focusing on their interplay with inflammatory and lipid-related markers. Methods This cross-sectional study encompassed 617 individuals diagnosed with ACS. Baseline characteristics, including inflammatory and lipid-related markers, were compared between individuals with non-severe (SYNTAX score ≤ 22) and severe (SYNTAX score > 22) coronary lesions. To evaluate both the impacts of Hcy and PCSK9 on coronary lesions severity, multivariate logistic regression along with mediation analyses were utilized. The robustness of the findings was validated by conducting subgroup analyses and sensitivity tests. Results Patients with severe conditions showed higher levels of Hcy, PCSK9, and inflammatory markers compared to non-severe cases. Both Hcy and PCSK9 levels were independently linked to a heightened risk of severe coronary lesions(ORs: 1.03–1.04 and 1.01–1.02, respectively, all P < 0.001). PCSK9 mediated 34.04% of Hcy’s effect on coronary lesion severity, whereas Hcy mediated 31.39% of PCSK9’s effect, indicating significant mutual mediation between these biomarkers. Subgroup analyses revealed consistent associations, with notable interactions based on creatinine levels for Hcy and gender, smoking status, and diagnosis for PCSK9. Sensitivity analyses confirmed the robustness of the mediation effects. Conclusions These findings emphasize the mutual mediating effects of Hcy and PCSK9 on coronary lesion severity in patients suffering from ACS. These results highlight the complex interactions between lipid metabolism and inflammation in the pathophysiology of ACS, suggesting that targeting both Hcy and PCSK9 may offer novel therapeutic strategies to mitigate severe coronary lesions among high-risk patients.